Designing Multicultural and Global Language Programs: Leveraging Digital Platforms to Foster Cultural Competence in Language Learning - Anggra Prima; Amine Meddah; Sara Al-Jabri (Yayasan Adra Karima Hubbi, 2026)
Background. In an increasingly globalized world, language learning programs must go beyond linguistic competence to include cultural competence. Digital platforms offer innovative solutions to incorporate cultural understanding into language learning, fostering multicultural awareness and cross-cultural communication skills. However, integrating these elements into digital language programs remains underexplored, despite its potential to enhance both language acquisition and cultural literacy. Purpose. This study aims to design multicultural and global language programs by leveraging digital platforms to promote cultural competence in language learning. The research seeks to explore how digital tools and platforms can be utilized to create immersive, culturally relevant learning environments that foster deeper cultural understanding while enhancing language skills. Method. A qualitative research design was employed, involving the development of a digital language program that integrates cultural modules using multimedia tools, virtual exchanges, and collaborative learning. Data were collected through participant feedback, surveys, and performance assessments before and after the program implementation. Results. The findings indicate that integrating cultural content into digital language programs significantly improved learners’ cultural awareness and language proficiency. Participants reported higher levels of engagement and a better understanding of cultural nuances through interactive, virtual exchanges and multimedia content. Conclusion. Digital platforms offer a valuable tool for creating multicultural and global language programs that enhance both language and cultural competence. These programs can play a vital role in preparing learners for effective cross-cultural communication in a globalized world.